Holistic insights from pollen omics: co-opting stress-responsive genes and ER-mediated proteostasis for male fertility. Issue 4 (2nd October 2021) - Sze, Heven; Palanivelu, Ravishankar; Harper, Jeffrey F; Johnson, Mark A
Abstract: Sexual reproduction in flowering plants takes place without an aqueous environment. Sperm are carried by pollen through air to reach the female gametophyte, though the molecular basis underlying the protective strategy of the male gametophyte is poorly understood. Here we compared the published transcriptomes of Arabidopsis thaliana pollen, and of heat-responsive genes, and uncovered insights into how mature pollen (MP) tolerates desiccation, while developing and germinating pollen are vulnerable to heat stress. Germinating pollen expresses molecular chaperones or "heat shock proteins" in the absence of heat stress. Furthermore, pollen tubes that grew through pistils at basal temperature showed induction of the endoplasmic reticulum (ER) stress response, which is a characteristic of stressed vegetative tissues. Recent studies show MP contains mRNA–protein (mRNP) aggregates that resemble "stress" granules triggered by heat or other stresses to protect cells. Based on these observations, we postulate that mRNP particles are formed in maturing pollen in response to developmentally programmed dehydration. Dry pollen can withstand harsh conditions as it is dispersed in air. We propose that, when pollen lands on a compatible pistil and hydrates, mRNAs stored in particles are released, aided by molecular chaperones, to become translationally active. Pollen responds to osmotic, mechanical, oxidative, and peptide cues that promote ER-mediated proteostasis and membrane trafficking for tube growth and sperm discharge. Unlike vegetative tissues, pollen depends on stress-protection strategies for its normal development and function. Thus, heat stress during reproduction likely triggers changes that interfere with the normal pollen responses, thereby compromising male fertility. This holistic perspective provides a framework to understand the basis of heat-tolerant strains in the reproduction of crops. Abstract : Pollen normally dehydrates to promote desiccation tolerance in pollen grains and then rehydrates to initiate germination; thus, further demands on these responses by heat stress reduce male fertility.